Transcriptome analysis of the hepatopancreas from the Litopenaeus vannamei infected with different flagellum types of Vibrio alginolyticus strains - Zhang, Jingwen; Liu, Kaifang; Gong, Xiaoxiao; Zhang, Na; Zeng, Yanhua; Ren, Wei; Huang, Aiyou; Long, Hao; Xie, Zhenyu (Frontiers in Cellular and Infection Microbiology, 2023)
Vibrio alginolyticus, one of the prevalently harmful Vibrio species found in the ocean, causes significant economic damage in the shrimp farming industry. Its flagellum serves as a crucial virulence factor in the invasion of host organisms. However, the processes of bacteria flagella recognition and activation of the downstream immune system in shrimp remain unclear. To enhance comprehension of this, a ΔflhG strain was created by in-frame deletion of the flhG gene in V. alginolyticus strain HN08155. Then we utilized the transcriptome analysis to examine the different immune responses in Litopenaeus vannamei hepatopancreas after being infected with the wild type and the mutant strains. The results showed that the ΔflhG strain, unlike the wild type, lost its ability to regulate flagella numbers negatively and displayed multiple flagella. When infected with the hyperflagella-type strain, the RNA-seq revealed the upregulation of several immune-related genes in the shrimp hepatopancreas. Notably, two C-type lectins (CTLs), namely galactose-specific lectin nattectin and macrophage mannose receptor 1, and the TNF receptor-associated factor (TRAF) 6 gene were upregulated significantly. These findings suggested that C-type lectins were potentially involved in flagella recognition in shrimp and the immune system was activated through the TRAF6 pathway after flagella detection by CTLs.